SOCIAL CLASS IN KEVIN KWAN’S CRAZY RICH ASIAN - Aisah Aura; Susi Ekalestari (JOURNAL OF LANGUAGE, 2023)
This research is aimed to analyze the protagonist’s social class in Kevin Kwan’s "Crazy Rich Asian." People are classified into different categories or levels in a similar position in the social hierarchy based on factors such as wealth, education, occupation, family background, and income. The protagonist’s social class is middle class, from which she, Rachel, gets the negative impact of her boyfriend’s family and friends, who come from the upper class. This research is completed using a descriptive qualitative method, in which the analysis and the findings are presented descriptively. The main data for this research are taken from the novel "Crazy Rich Asians." The findings of this research show that the social class of the protagonist is middle class, which is characterized by the way she dresses, her family background, and her amazement at the views of places that the upper class are used to visiting. Furthermore, the protagonist suffers because she is from the middle class. She gets mockery or ridicule from her friends, and she is rejected to be married by Nick, who comes from the upper class.